Corporate social responsibility and R&D investment in Chinese firms with financial constraints as a mediator - Yingxiang, Cheng; Teruki, Neilson; Taasim, Shairil Izwan Bin (Asian Economic and Financial Review, 2025)
This study explores the effects of corporate social responsibility (CSR) on Research and development (R&D) investment with a specific focus on the role of financial constraints as a mediating factor. Using 23962 firm-year observations from Chinese A-share listed companies from 2011 to 2020 as a sample, this study explores the internal links between CSR, financial constraints, and firms’ R&D investment. This study empirically examines the relationship between CSR and R&D investment using a double-fixed-effect Ordinary Least Squares (OLS) regression method. It validates the relationship with robustness checks, including alternative periods, alternative measures, and Two-stage Ordinary Least Squares (2SLS) regression for endogeneity concerns. The results show that CSR promotes R&D investment. Furthermore, using the Sobel test, this study examines the mediating effects of financial constraints on the relationship between CSR and R&D investment. The empirical results verify that CSR promotes R&D investment by alleviating firms’ financial constraints. This suggests that firms can obtain more financing support by fulfilling CSR and providing financial support for fostering R&D investment. The findings offer valuable perspectives for corporate decision-makers, policymakers, and scholars, emphasizing CSR's pivotal role in shaping R&D investment and promoting sustainable economic progress in China's dynamic market environment.